PENINGKATAN HASIL BELAJAR SISWA SD DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE GROUP INVESTIGATION - Susanti, M.Pd, Dini (Menara Ilmu, 2017)
IPS Learning is focused on the teacher as the primary source of learning, then a lecture tochoice in learning, so students get bored and think of learning IPS unattractive andconsequently, the value of students is low. This study aimed to describe the learning outcomesof students in learning by using the IPS model of cooperative learning GI type. Studentlearning outcomes cycles 1 and 2 meetings I average 53.0 and 68.6. Cycle II meetings 1 and 2the average value of 82.0 and 82.3. The study uses a model of GI, can improve studentlearning outcomes in social studies learningKeywords: Group Investigation Model, Student Results